Exercício dos direitos de ação e petição no juizado especial de Santa Rita a partir da pandemia de Covid-19 - Olivera, Anderson Fagundes Xavier de (2023)
The COVID-19 pandemic, which began in 2020, imposed the adoption of measures that have impacted the functioning of numerous activities, among them those provided by the Judiciary. Despite the massive adoption of electronic platforms for processing cases, thus allowing the continuity in the distribution and promotion of demands, it appears that certain procedural actors, legally authorized to litigate in court without legal assistance, would be excluded from the Electronic Judicial Process, as they generally do not have a digital certification for this purpose. In this context, the problem faced in the present research consists of cataloging the mechanisms adopted by the Small Claim Court of the County of Santa Rita/Paraíba, from the global outbreak of the new coronavirus, to ensure the rights of action and petition of the parties that, by permission of Law nº 9.099/95, can act autonomously. Having identified these implemented actions, the general objectives of this work are placed in examining their degree of efficiency in safeguarding the rights of action and petition of autonomous claimants, as well if, based on these measures, new forms of exercise of action and petition rights can be identified. As more specific pretensions, this study objectify: i) identify a possible drop in the number of lawsuits filed by parties without lawyers; ii) to determine the means made available by the researched court to the autonomous claimants so that they could initiate their respective processes; iii) verify any change in the profile of the demands presented to the assessed jurisdictional unit; iv) compare the level of acceptance of claims made by parties without lawyers before and after the pandemic; v) to catalog any innovation in the exercise of the rights of action and petition of autonomous claimants based on the measures implemented by the Special Court of Santa Rita with the advent of the health emergency. For this purpose, a research was implemented in four stages. Initially, the literature considered most relevant about the fundamental right to access to justice was revisited. In a second moment, the research was dedicated to the survey of the normative measures adopted within the scope of the Judiciary Power due to the health emergency, with the respective repercussions on the judicial services offered. In a third moment, the study sought to catalog the ways of inaugurating and boosting demands made available by the Small Claim Court of Santa Rita, before and after the pandemic period, contextualizing them, including, with actions adopted by other units of similar attribuitions. In the fourth and last moment of the research, several procedural data of the researched jurisdictional unit were recorded, in order to understand the procedural implications of the administrative reorganizations adopted. This dissertation concluded, initially, by not including the perspectives of autonomous plaintiffs in legal theories involving access to justice. This study also inferred, through content analysis of the various procedural statistics raised, that the right of petition of the own cause litigants remained protected, remaining the evaluation of the safeguard of the right of action, despite an identified drop in the number of processes distributed, indefinitely, by require more indepth studies, including field and opinion research involving self-employed claimants in Santa Catarina. Finally, a possible innovation related to the right of petition was pointed out, with the identification of procedural manifestations made through voice messages and video recordings.